Strategi Pengembangan Pemasaran Batu Andesit (Studi Kasus pada PT Duta Keluarga Imfaco, Bogor Jawa Barat) - Imron, Tubagus; Nazli, Rizal Syarief Sjaiful; Raharja, Sapta (Institut Pertanian Bogor, 2018)
Andesite stone mining activities in Bogor area is now growing, one of the andesite stone processing business is PT Duta Keluarga Imfaco located in Bogor Regency, West Java. The economically valuable andesit stone is expected to be the mainstay of the income of the surrounding community, characterized by the increasing market demand and the growing interest of the community towards andesite stone. The purpose of this study are (1) to identify internal and external factors of PT Imfaco Family Ambassador; (2) Developing appropriate market development strategies; and (3) Develop alternative strategies of andesite stone marketing development. The study used descriptive and analytic methods that are case studies. Determination of respondents with purposive sampling method, with consideration that mastered the problems to be asked. Data analysis with IFE and EFE matrix to identify internal and external factor of company, then mapping with IE matrix, to see company position. Preparation of strategy with SWOT matrix, yield several alternative strategies that can be implemented. The final stage with the QSP matrix, to determine the priority of the most appropriate strategy to be implemented. Based on the results of IFE and EFE matrix analysis, indicates the company is in a stable position in responding to external situations. The result of analysis with IE matrix, company is in quadrant V, that is growth and stability, where strategy that can be done is market penetration and business development. Results of analysis with SWOT matrix obtained alternative strategies that can be implemented and with the QSP matrix obtained the most appropriate strategy to be implemented in order to develop the company's marketing strategy is to expand the marketing network.